Absence of influenza vaccination among high-risk older adults in Taiwan - Li Ying-Chun (BMC, 2010)
Abstract Background Older adults, who often have more than one chronic disease, are at greater risk of influenza and its complications. However, because they often see physicians for other more pressing complaints, their physicians, focusing on one condition, may forget to suggest preventive measures for other diseases such as influenza. This study investigates what major factors affect an older adult with more than one chronic condition missing a vaccination opportunity. Methods Retrospectively reviewing a nationally representative random sample of medical claims from Taiwan's National Health Insurance Research Database during the period 2004 - 2006, we first identified patients sixty-five years or older who had visited physicians. Each patient was assigned a proxy for health status, the Charlson Comorbidity Index (CCI) score. An older claimant was defined has having "absence of a vaccination" when he or she had visited a physician during an influenza season but did not receive an influenza vaccination. Multivariate logistic regression was performed to estimate how likely it would be for older adults with various CCI scores to miss a vaccination. Results Out of 200,000 randomly selected claims, 20,923 older adults were included in our final analysis. We found older adults with higher CCIs to be more likely to have an absence of vaccination (p < 0.01). Our multivariate logistic regression results revealed CCI to be the greatest predictor of absence of vaccination, after controlling for individual factors and medical setting. Older adults with CCI scores three or higher were nearly five times more likely to miss a vaccination than those with a CCI of zero [OR: 4.93 (95%CI, 4.47-5.42)]. Those with CCIs of one and two were 2.53 and 3.92 times more likely to miss vaccination than those with a CCI of zero [OR 2.53 (95%CI, 2.26-2.84) and OR 3.92 (95%CI, 3.51-4.38), respectively]. Conclusions The greater the number of certain comorbid conditions, the greater the likelihood a flu vaccination will be missed. Physicians would be well advised to not let the presenting problems of older patients distract from other possible health problems that might also need attention, in this case influenza vaccinations.